The Critique of claim the book of “Nixon, Kissinger and Shah’ about Relations between Shah and the U.S.A in Cold War” - Alireza Mollaiy Tavany (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book ‘Nixon, Kissinger and Shah: Relation between Iran and the U.S.A in Cold War’ is a very marketable book in Iran’s market. There are very important claims about the nature of Iran’s relations with the U.S.A. The main claim is this question whether Shah acted independently toward west in the political area. Did Shah alter relations of ruler – obedience in Nixon’s period and oblige U.S.A to follow Iran’s regional politics? Studying about the importance of this claim and its critique of that are the main purposes of this article. This article concludes several phases of relation between Iran and the U.S.A in decades 1950 until 1970. Shah used international’s opportunity that altered nature of Iran’s relation with the U.S.A in several phases and played different roles. But, these operations did not alter the nature of the relations between Iran and the U.S.A. because when this relation altered the context and international’s opportunities, the relations between Iran and the U.S.A would come back the to ruler – obedience.